Landmines and human security : international politics and war's hidden legacy - Matthew, Richard A., 1959-; McDonald, Bryan (Bryan L.); Rutherford, Ken, 1962- (SUNY series in global politics., 2004)
"An impressive array of activists, scholars, government officials, journalists, and landmine victims themselves are gathered here to tell the story of the International Campaign to Ban Landmines (ICBL). Organized in the early 1990s, the ICBL is a network of more than one thousand nongovernmental organizations worldwide, working for a global ban on landmines. It was an important force behind the treaty to ban antipersonnel landmines that was signed in Ottawa in 1997, and which led to its being awarded the 1997 Nobel Peace Prize, along with its coordinator."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved